Control-based algorithm for the management of IEEE 802.11e priorities within a Wireless Networked Discrete Control System - Habib, G; Pétin, J F; Divoux, T (2010 Conference on Control and Fault-Tolerant Systems (SysTol), 2010)
This paper deals with the evaluation of Discrete Control Systems whose implementation is distributed among Programmable Logic Controllers (PLC) and remote Input/Output devices communicating through a Wireless Network. Using wireless communication in these applications, called Wireless Networked Discrete Control System (WNDCS), offers many advantages such as a greater mobility and reduced wiring costs, but also several disadvantages such as transmission delay, jitter phenomena or loss of messages due to nondeterministic features of wireless communication. These features may have a negative impact on the behaviour of the control applications, and especially on the temporal performance and dependability requirements that a control system usually has to face. This paper proposes an algorithm for the management of the IEEE 802.11e priorities with regards to control needs in order to increase the performance of the WNDCS. Efficiency of the proposed algorithm is shown using OPNET simulations of a case study.